2015
DOI: 10.1176/appi.ajp.2014.14020263
|View full text |Cite
|
Sign up to set email alerts
|

Association of CRP Genetic Variation and CRP Level With Elevated PTSD Symptoms and Physiological Responses in a Civilian Population With High Levels of Trauma

Abstract: Objective Increased systemic inflammation is associated with stress-related psychopathology. Specifically, levels of the pro-inflammatory marker C-reactive protein (CRP) are increased in individuals with posttraumatic stress disorder (PTSD). Furthermore, single nucleotide polymorphisms (SNPs) in the CRP gene are associated with CRP levels, risk for cardiovascular disease and obesity. We examined whether polymorphisms within the CRP gene and increased CRP levels are associated with PTSD symptoms and fear physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 63 publications
(88 reference statements)
4
122
4
1
Order By: Relevance
“…Similar findings have been described in rodents (Avitsur et al, 2006;Brenhouse and Thompson, 2015;Hennessy et al, 2010b). Furthermore, early-life immune activation has been linked to greater neuroendocrine activation in the context of subsequent stressors (Shanks et al, 1995(Shanks et al, , 2000, and higher baseline levels of inflammation have been associated with greater stressinduced responses in animal models (Hodes et al, 2014) and humans (Eraly et al, 2014;Michopoulos et al, 2015). On the other hand, there is initial evidence that genes coding for pro-inflammatory cytokines could moderate the effect of childhood trauma on brain function.…”
Section: Synergysupporting
confidence: 64%
See 1 more Smart Citation
“…Similar findings have been described in rodents (Avitsur et al, 2006;Brenhouse and Thompson, 2015;Hennessy et al, 2010b). Furthermore, early-life immune activation has been linked to greater neuroendocrine activation in the context of subsequent stressors (Shanks et al, 1995(Shanks et al, , 2000, and higher baseline levels of inflammation have been associated with greater stressinduced responses in animal models (Hodes et al, 2014) and humans (Eraly et al, 2014;Michopoulos et al, 2015). On the other hand, there is initial evidence that genes coding for pro-inflammatory cytokines could moderate the effect of childhood trauma on brain function.…”
Section: Synergysupporting
confidence: 64%
“…Of note, these associations were not simply explained by comorbid depression (Passos et al, 2015). In addition, genetic (Michopoulos et al, 2015) and longitudinal (Eraly et al, 2014) studies suggest that inflammation is a preexisting vulnerability factor for the development of PTSD in trauma-exposed individuals rather than simply a correlate of subjective distress, disease severity, or maladaptive coping strategies following PTSD onset.…”
Section: Observational Studies In Humansmentioning
confidence: 95%
“…Pervanidou et al (2007), for example, reported that children with higher concentrations of plasma IL-6 following a motor vehicle accident had a greater chance of developing PTSD compared with children who did not have elevated IL-6 after the accident or controls. Furthermore, Michopoulos et al (2015) and Heath et al (2013) reported that CRP concentration was correlated with PTSD symptom severity and duration, such that PTSD patients with high, compared with low, CRP had greater symptom severity and duration (Heath et al, 2013;Michopoulos et al, 2015). There is, therefore, a growing body of clinical studies establishing the association between stressor exposure, inflammation, and mood disorders.…”
Section: Clinical Evidence Linking Inflammation and Stress-related Momentioning
confidence: 99%
“…In several meta-analyses of this literature, the most well-documented and reproducible findings have included increases in peripheral blood concentrations of the cytokines interleukin-6 (IL-6) and tumor necrosis factor (TNF) and the acute-phase reactant C-reactive protein (CRP) (Howren et al, 2009;Dowlati et al, 2010;Haapakoski et al, 2015). In addition to increases in inflammatory markers in depressed subjects, a number of polymorphisms in genes associated with inflammation, including IL-1β, IL-6, and TNF, as well as CRP, have been linked to the development of mood and anxiety disorders as well as treatment response (Bufalino et al, 2012;Michopoulos et al, 2015). Epigenetic changes in genes involved in the regulation of immune responses including FK506 binding protein 5 (FKBP5) have also been implicated in anxiety disorders and the response to stress.…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 99%
“…Studies have been conducted and are underway using both adrenergic antagonists and synthetic glucocorticoids in the context of acute trauma to prevent development of PTSD (Amos et al, 2014). Nevertheless, although increased inflammatory markers including CRP have been shown to predict the subsequent development of PTSD (Eraly et al, 2014;Michopoulos et al, 2015), no studies have determined whether those individuals with increased inflammatory markers are the ones who might be most likely to respond to adrenergic or glucocorticoid agonists. Moreover, whether the success of these interventions is in part due to inhibition of stress-induced inflammatory responses or even through glucocorticoid-mediated trafficking of neuroprotective T cells to the brain has yet to be established.…”
Section: Reviewmentioning
confidence: 99%